Silniejsze procesy rozwojowe w gospodarstwach towarowych Śląska Opolskiego - Bisaga, Anna (The Stronger Developmental Processes in the Trading Farmholdings of Opole Silesia, 2006)
The research into the typology of farm holdings in the regional framework indicates an occurrence, in the agriculture of certain regions of Poland, of stronger developmental processes. In the case of Opole Province their diagnosis is contained in the results of a research project concerning changes in the organization and productivity of the agriculture of the region. The research was carried out at consecutive stages in the years 1990, 1992, 2000 and 2004. The essence of all the changes in the organization of individual farming consists in searching for economic effectiveness of agricultural activities carried out in the farm holding. It follows from the gathered research material that the rise in productivity can be attained in different types of farm holdings. At the same time, principles of good farming practice can be observed successfully. It was found out that the type of farm holding had eventually been adjusted to the natural conditions of production, as well as to available labour resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 91-97